The Application of Stimuli-Sensitive Actuators Based on Graphene Materials - Xue, Jiangli; Gao, Zhaoshun; Xiao, Liye (Frontiers in Chemistry, 2019)
Graphene-based materials that can spontaneously response to external stimulations have triggered rapidly increasing research interest for developing smart devices due to their excellent electrical, mechanical and thermal properties. The specific behaviors as bending, curling and swing are benefit for designing and fabricating the smart actuation system. In this minireview, we overview and summarize some of the recent advancements of stimuli-responsive actuators based on graphene materials. The external stimulus usually is as electrical, electrochemical, humid, photonic and thermal. The advancement and industrialization of graphene preparation technology would push forward the rapid progress of graphene-based actuators and broaden their application including smart sensors, robots, artificial muscles, intelligent switch and so on.